Knowledge and perception of pharmacy students about complementary and alternative medicine: Findings from a Malaysian Public University - Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod; Hadijah, SH; Haniki, NM; Alshami, Abdulkareem Mohammed; Jawad, AI; Hassali, MA (Elsevier, 2014)
This study aimed to explore the knowledge, perception and attitude of pharmacy students towards complementary and alternative medicine (CAM).